Equity in Distance Education During COVID-19 - Tamika K Williams; Robert W McIntosh; William B. Russell (Research in Social Sciences and Technology- OpenED Network, 2021)
The COVID-19 pandemic forced districts, schools, and teachers to mobilize in order to deal with the digital inequities that have existed for decades. At the beginning stages of technological advances in education, the so-called digital divide related more to access to technology and equipment. Utilizing the phenomenological approach to qualitative research, this study examines the experiences of educators who served students with differing experiences and needs during the COVID-19 pandemic. Total of 14 (N) educators (including adminstrators, teachers, and counselors) participated likert style questionaires. 11 of 14 participated in focus group interviews. Findings are shared and conclusions are drawn.